Pengolahan Daun Kelor sebagai Produk Olahan Lokal yang Berdaya Saing - Putri Ulfa Kamalia; Anasyiah Nur Hamidah; Jasuli; Hendra Kunhardianto (Jurnal Pemberdayaan Masyarakat, 2023)
Moringa leaves are rich in potential benefits and are easy to find in Sarirejo Village, Mojosari District, Mojokerto Regency. At this location there is a community organization for Family Empowerment Development (PKK) which consists of 50 members. The professions of the PKK members in Sarirejo Village are varied,, but most of the members are housewives. Because Moringa leaves are very abundant but have not been utilized properly, we held training on processing Moringa leaves to empower PKK women so that they have the skills and are interested in exploiting the existing potential. Â The method of implementing activities is carried out through several stages, namely the preparation stage, implementation stage and evaluation stage. The PKK members were trained to process Moringa leaves into Moringa dry cakes, Moringa pudding and Moringa noodles. Based on the evaluation results of the training implementation, it can be stated that this training was very interesting, participants did not find it difficult in the product manufacturing process, this training was very useful and the participants were interested in continuing the skills they had obtained from this training into a sustainable and competitive business.